PELAKSANAAN PENGANGKATAN ANAK DALAM PERPEKTIF PERATURAN PEMERINTAH REPUBLIK INDONESIA NOMOR 54 TAHUN 2007 DI KABUPATEN BANTUL - Sri Suwarni (Kajian Hukum, 2017)
The purpose of this study is to investigate the implementation of the Indonesian Government Regulation No. 54 Year 2007 in Bantul, and also to find out the problems that occur in the practice of adoption in Bantul.This research was conducted by library research and field research. In the literature research to use the means of documents study for secondary data, while the field research was conducted to obtain primary data with qualitative approach with interviews. Data obtained from the literature research and field research analyzed qualitatively. The data is further described by the descriptive method of analysis, that in discussing the problems done by identifying, analyzing and interpreting the data that has been acquired to be concluded.Based on the survey results revealed that the Indonesian Government Regulation No. 54 Year 2007 on the Implementation of Child Adoption basically been implemented in practice the implementation of child adoption either through Decision of District Court and Religious Courts In Bantul District, in fact not all applications for adoption for Muslim proposed through the Religious Courts, but some also proposed through the District Court. The Determination of Adoption in the Religious Court, firstly, based on the Indonesian Government Regulation No. 54 Year 2007 on the Implementation of Child Adoption, secondly, is also based on Presidential Decree No. 1 Year 1991 About the Compilation of Islamic Law.Problems that occur in the practice of adoption in Bantul district which are the practice of adoption which is done by custom only and not applied for court determination that can cause problems, especially a civil matter after his adoptive parents died. Another example is the practice of deviating adoption from the existing provisions; especially adoptions are taken directly from the biological parents of the child since birth, then the birth of the child is registered in the name of his adoptive parents to obtain a birth certificate of the child. Keywords: Adoption, child, and the Indonesian Government Regulation No. 54 Year 2007.